The Effect of Organizational Communication, Motivation and Work Discipline on Employee Performance of the UMKM Cooperative Office of Medan City - Kahar Batubara, Abdul; Hermansyur; Pitono (Journal Boas : Business, Economics, Accounting And Management, 2024)
This research aims to analyze the influence of organizational communication, motivation and work discipline on employee performance. The total population in this study was 70 people, and by using saturated sampling techniques a sample of 70 people was obtained. The analysis technique used is multiple linear regression. The results of the research show that organizational communication has a significant effect on the performance of employees of the Medan City UMKM Cooperative Service, motivation has a significant effect on the performance of employees of the Medan City UMKM Cooperative Service, work discipline has no effect on the performance of employees of the Medan City UMKM Cooperative Service. Simultaneously, it shows that organizational communication, motivation and work discipline have a significant effect on the performance of employees of the Medan City UMKM Cooperative Service,